Peranan Dakwah Kismis Purwakarta secara Online dalam Menyiarkan Islam - Syifa Fauzi Karimah (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. The development of the times brought preaching to the online media. Dakwah KISMIS (Islamic Studies Every Thursday) in Purwakarta carries out its Islamic broadcasts using various social media with a research focus on the role of online preaching of KISMIS in Purwakarta in broadcasting its Islamic messages. This research uses descriptive qualitative methods and is analytical in nature. Where the research analyzes the results of interviews with respondents who take part in KISMIS through online media from various social media to spread Islamic messages which contain faith, sharia and morals. In the results of this study, it is concluded that the role of the message of tauhid KISMIS does not play a role because there are several differences of opinion regarding faith in qadha and qadar regarding unhabbed prayer. It is the same as the role of the Shari'a message which is considered to have less role, because there are many differences of opinion and views regarding prayer and the intention to fast. Whereas in the role of messages regarding morals it is also considered to have less role, because there are different views on the morals of children to parents of different religions who have died and manners to tormented animals. So it can be said that the role of online KISMIS is insufficient in broadcasting Islam in Purwakarta due to the lack of meaning of the da'wah messages conveyed to respondents in the study so that it gives different views and understandings with some respondents who are followers of KISMIS through online media. Abstrak. Berkembangnya zaman membawa dakwah masuk dalam media online. dakwah KISMIS (Kajian Islam Setiap Kamis) di Purwakarta melakukan syiar Islamnya dengan menggunakan berbagai media sosial. Penelitian berfokus pada peranan dakwah KISMIS di Purwakarta secara Online dalam menyiarkan pesan-pesan Islamnya. Penelitian ini menggunakan metode kualitatif deskriptif dan bersifat analisis. Dimana penelitian menganalisis hasil dari wawancara pada responden yang mengikuti KISMIS melalui media online dari berbagai media sosial untuk menyiarakan pesan Islam yang berisikan akidah, syariat dan akhlak. Dalam hasil penelitian ini mendapatkan kesimpulan mengenai peranan pesan tauhid KISMIS kurang berperan karena ada beberapa perbedaan pendapat mengenai iman kepada qadha dan qadar perihal doa yang belum terijabah. Sama dengan peranan pesan syariat yang dinilai kurang berperan, karena ada banyaknya perbedaan pendapat dan pandangan mengenai shalat dan niat berpuasa. Sedangkan dalam peranan pesan mengenai akhlak juga dinilai kurang berperan, karena ada perbedaan pandangan mengenai akhlak anak kepada orang tua berbeda agama yang sudah meninggal dan adab kepada hewan yang terdzalimi. Sehingga dapat dikatakan kurang berperannya KISMIS secara online dalam menyiarkan Islam di Purwakarta dikarenakan adanya beberapa makna pesan dakwah yang kurang tersampaikan kepada responden dalam kajian sehingga memberikan perbedaan pandangan dan pemahaman dengan beberapa responden yang menjadi pengikut KISMIS melalui media online.